Third trimester oligohydramnios and pregnancy outcome in a tertiary care hospital - Hota, Basanta Manjari; Vijayasree, M.; Movva, Naimisha; Lakshmi Indu, Mudragada; Reddy, Nayana Jyothsna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Amniotic fluid has an important function in achieving a successful pregnancy outcome. An amniotic fluid Index of <08 cm is considered oligohydramnios and is expected to result in an adverse pregnancy outcome. Many of its etiologies are preventable and treatable with early diagnosis and timely intervention. Methods: The present retrospective, cross-sectional study was conducted in the Department of Obstetrics and Gynecology, Mamata Medical College, Khammam, Telangana, from 1st January 2024 to 31st December 2024, including all eligible oligohydramnious cases. Detailed patient data were collected from the Department of Medical Records, analyzed using standard descriptive statistics, and the significance of the correlation of the degree of oligohydramnios on pregnancy outcome was determined using p-values in Microsoft Excel 21. Results were discussed critically and compared with those of other studies. Results: A total of 74 oligohydramnios cases constituted an incidence of 05.90%. Mean age was 24.20±04.21years, 79.73% caesarean delivery, <7 Apgar score at 01 min in 60.81%, and 58.11% at 05 min, 56.76% low birth weight, and neonatal intensive care unit (NICU) admission was 56.76%. Significant differences were found in mode of delivery, meconium-stained liquor, Apgar score, and NICU admission between the two groups of oligohydramnios. Conclusions: Adverse pregnancy outcome in the third trimester oligohydramnios can be reduced, with adequate antenatal care, though not completely preventable. The study aimed to determine the incidence of oligohydramnios in the third trimester of pregnancy, the contributing factors prevalent in the region, and the effect on pregnancy outcome.